2021
DOI: 10.21203/rs.3.rs-257411/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical efficacy and immunity of a novel immune-modulatory peptide vaccine against IDO/PD-L1 (IO102/IO103) in combination with nivolumab in patients with metastatic melanoma

Abstract: Anti-PD-1 (aPD1) therapy is an effective treatment for metastatic melanoma (MM); however, >50% of the patients progress due to resistance. Improved combination therapies enhancing aPD1 efficacy without leading to increased toxicity are needed. In this non-randomized phase I/II study (ClinicalTrials.gov: NCT03047928), we treated 30 aPD1 naive MM patients with a novel immune-modulatory vaccine (IO102/IO103) activating indoleamine 2,3-dioxygenase (IDO) and programmed death ligand-1 (PD-L1) specific T-cells com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…After intravenous administration in melanoma patients as single agent or in combination with anti PD-1 antibody, FixVac produces a clinical response rate in 12% and 35% of patients, respectively, with a good safety profile ( 14 ). Similarly, a long peptide vaccine targeting indoleamine-2,3-dioxygenase 1 (IDO)/PD-L1 (IO102/103) in combination with the anti PD-1 antibody nivolumab in a phase 1b/2 study in 30 naïve treatment advanced melanoma patients demonstrated 80% of clinical objective responses, including 43% of complete responses ( 15 ). Recently, data from a preclinical study compared in animal breast cancer models, the antitumoral effect of a personalized vaccine versus a vaccine based on the use of shared antigens showed similar antitumoral activity.…”
mentioning
confidence: 99%
“…After intravenous administration in melanoma patients as single agent or in combination with anti PD-1 antibody, FixVac produces a clinical response rate in 12% and 35% of patients, respectively, with a good safety profile ( 14 ). Similarly, a long peptide vaccine targeting indoleamine-2,3-dioxygenase 1 (IDO)/PD-L1 (IO102/103) in combination with the anti PD-1 antibody nivolumab in a phase 1b/2 study in 30 naïve treatment advanced melanoma patients demonstrated 80% of clinical objective responses, including 43% of complete responses ( 15 ). Recently, data from a preclinical study compared in animal breast cancer models, the antitumoral effect of a personalized vaccine versus a vaccine based on the use of shared antigens showed similar antitumoral activity.…”
mentioning
confidence: 99%